Hypoglycemia as a Pathological Result in Medical Praxis - Bjelakovic, G.; Stojanovic, I.; Jevtovic-Stoimenov, T.; Lj.Saranac; Bjelakovic, B.; Pavlovic, D.; Kocic, G.; Bjelakovic, B.G. (IntechOpen, 2011)
None